2003
DOI: 10.1038/nsb894
|View full text |Cite
|
Sign up to set email alerts
|

Extensive conformational sampling in a ternary electron transfer complex

Abstract: Here we report the crystal structures of a ternary electron transfer complex showing extensive motion at the protein interface. This physiological complex comprises the iron-sulfur flavoprotein trimethylamine dehydrogenase and electron transferring flavoprotein (ETF) from Methylophilus methylotrophus. In addition, we report the crystal structure of free ETF. In the complex, electron density for the FAD domain of ETF is absent, indicating high mobility. Positions for the FAD domain are revealed by molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
225
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(235 citation statements)
references
References 25 publications
8
225
0
Order By: Relevance
“…The ETF docking site is relatively simple, and because of the conformational flexibility of domain II, the relative positioning of the docking site and the electron transfer site has few restraints. Removal of Leu␤ 194/195 either by mutagenesis or limited proteolysis (8) leads to impaired electron transfer, supporting further the hypothesis that all ETFs interact with their partners via the recognition loop. On the other hand, mutagenesis of the conserved Arg␣ 237/249 , or of residues proposed to transiently interact with Arg␣ 237/249 , has led to very varied effects on reaction rates with different partners.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The ETF docking site is relatively simple, and because of the conformational flexibility of domain II, the relative positioning of the docking site and the electron transfer site has few restraints. Removal of Leu␤ 194/195 either by mutagenesis or limited proteolysis (8) leads to impaired electron transfer, supporting further the hypothesis that all ETFs interact with their partners via the recognition loop. On the other hand, mutagenesis of the conserved Arg␣ 237/249 , or of residues proposed to transiently interact with Arg␣ 237/249 , has led to very varied effects on reaction rates with different partners.…”
Section: Resultssupporting
confidence: 52%
“…This is clearly indicative of a "ball-and-socket" type of motion, where MCAD and the ordered regions of ETF form the socket in which the FAD domain can apparently move freely within the conformationally allowed space. Similar molecular motions occur in the bacterial ETF⅐TMADH complex (8) and also within a single protein chain (e.g. the Escherichia coli 5Ј-nucleotidase (22)).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…2b). This model is consistent with the proposed role of the same region in the structurally related cytochrome P450-BM3 (Sevrioukova et al, 1999) and reminiscent of those found in multiple redox centers containing proteins (Zhang et al, 1998,Lennon et al, 2000,Leys et al, 2003. Additionally, this swinging FMN domain mechanism would account for the slow rate of inter-module electron transfer in NOS.…”
Section: Ros and Nitric Oxide Synthasesupporting
confidence: 73%